An in situ grazing incidence X-ray scattering study of block copolymer thin films during solvent vapor annealing - Gu, Xiaodan (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.